Determinants of international market reach of entrepreneurs: Examining the effects of access to technology - Alinsunurin, Jason P. (Animo Repository, 2013)
In this paper, we analyzed the factors affecting the international market reach of entrepreneurs using the Global Entrepreneurship Monitor (GEM) data. Our motivation is the noticeably low share of international market reach of entrepreneurs in the Philippines compared with countries with similar levels of income and economic openness. We performed multinomial logistic regression to show the importance of access to new technologies in increasing access to international markets. We also underscore the importance of a policy that will gear firms in Asean to greater cross border marketing, especially in the light of impending greater degree of economic integration and cross border trade. This can be done by specifically highlighting country-specific socio-cultural and political dynamics which directly influence the choice to explore international markets. We also saw statistically insignificant impacts of age and gender, and present evidence of the relevance of skill matching of entrepreneurs to exploring international markets.